On Memory, History, Concious and Unconscious. Contemporary Research in Memory Studies: Contemporary Research in Memory Studies - Švaříčková-Slabáková, Radmila (Dějiny – teorie – kritika, 2007)
The article tries to analyze contemporary research in memory studies, above all on the example of Anglo-saxon and French historiographies. First, it traces the contribution of already several generations of memory studies, providing a brief comparison with the Czech historiography of memory. Next, it gives examples of different approaches towards two key concepts – memory and history, analyzing their relationship in Nora’s Les Lieux de Mémoire and Halbwachs’s studies on memory. Individual and collective memories and their possible interpretations are treated with respect to the psychological approach towards memory and the importance of unconscious for historians is demonstrated on the works of C. G. Jung, A. Toynbee, L. Passerini and V. de Gaulejac. The article concludes focusing on contemporary oral history research stated that collective memory studies and oral history studies convert which is challenging for individual memories and individual remembering, the original key concepts of oral history studies.